beta-Adrenoceptor stimulation of exocrine secretion from the rat pancreas. - Furuta, Y (1978)
1 Effects of catecholamines given intravenously on exocrine secretion from the pancreas were investigated in anaesthetized rats. The flow rate of pancreatic juice under resting conditions was 11.1 +/- 3.2 microliter per hour in 100 animals. 2 Dopamine (0.3--3 mg/kg) and isoprenaline (1--10 microgram/kg) induced almost the same increase in the pancreatic secretion, so that dopamine was 300 times less potent than isoprenaline. The relative potency of the two amines for stimulation of pancreatic secretion was equivalent to that for beta-stimulation of the contractile force of the left ventricle in vivo. 3 Propranolol (0.5 mg/kg) antagonized completely the dopamine- and isoprenaline-induced stimulation of the pancreatic secretion. 4 Haloperidol (10 mg/kg) failed to suppress the secretory effect of dopamine on the exocrine pancreas but abolished the dopamine-induced hypotension. 5 The dopamine-induced secretion was not modified by atropine (3 mg/kg), phenoxybenzamine (3 mg/kg), vagotomy or pithing. 6 Adrenaline and noradrenaline (10 microgram/kg) induced secretion after phenoxybenzamine treatment (3 mg/kg). 7 It is suggested that the rat pancreas has a stimulatory beta-adrenoceptor mechanism of exocrine secretion.